Hubungan Rencana Karir dengan Motivasi Menyelesaikan Studi pada Mahasiswa S1 Bimbingan Konseling - Yuniarto, Ardian (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
Final year students at the stage of development of early adulthood. One task at this stage is already to plan a career choice. But as student, completed the study is a phase that must be passed, wich was made reasearch that addresses the correlation between completed the study with a plan of career choice. This study aimed to determine the profile of motivation in completing the study and career  choice plan for students, then to determine the correlation between both of them. The method used in this research is descriptive quantitative survey methods. The subjects of this research were all undergraduate students of Guidance and Counseling dept. Unnes class of 2010 related to career choice plan and motivation in completing the study. Data was collected using scales of career choice plan and scales of motivation in completing the study. Data were analyzed using percentages description and product moment method. The average result of motivation in completing the study was included in the high category (75,60%). While the profile of career choice plan in overall was included in the medium category (68,50%). The correlation experiment results between career choice plan and motivation in completing the study produced numbers r count = 0,656 > rtable = 0.3357. The importance is career choice plans correlate with motivation in completing the study on undergraduate students of Guidance and Counseling department of Semarang State University class of 2010